FROM FRAGMENTATION TO INTEGRATION:A MULTI-PREMIUM VALUATION OF ALBANIA’S EQUITY MARKET IN A WESTERN BALKANS COMPARATIVE CONTEXT (The South East European Journal of Economics and Business, 2026)
This paper applies the Frontier Market Valuation Model (FMVM), a multi-premium valuation framework, to estimate equity market risk in Albania, a South-East European economy with persistently underdeveloped capital markets. In environments where equity trading is thin and market-based price discovery is weak, conventional asset-pricing models such as CAPM and CRP-augmented approaches tend to understate the true cost of equity. FMVM addresses this limitation by decomposing the required return on equity into sovereign, liquidity, behavioral, and institutional quality premiums. Using quarterly data from 2015 to 2024, the analysis shows that Albania’s implied equity risk premium averages around 20%, substantially exceeding estimates derived from CRP-based benchmarks. While sovereign risk remains an important component, non-sovereign factors—particularly governance quality and sentiment-driven market frictions—exert statistically significant effects on the required return. Chronic illiquidity, although less influential in time-series regressions, operates as a persistent level constraint that elevates equity financing costs. Comparative evidence from selected Western Balkan peers positions Albania toward the higher-risk end of the regional spectrum. Overall, the findings demonstrate FMVM’s value as a diagnostic valuation tool for frontier markets and highlight policy-relevant reform channels through which equity financing costs can be reduced and capital-market credibility strengthened.